Chemical enhancement effects on protoporphyrin IX surface‐enhanced Raman spectra: Metal substrate dependence and a vibronic theory analysis. (13th December 2020) - McNeely, James; Ingraham, Harrison M.; Premasiri, W. Ranjith; Ziegler, Lawrence D.
Abstract: Surface‐enhanced Raman spectra (SERS) of protoporphyrin IX (PPIX) and analogous metal‐containing PPIX compounds excited at 785 nm exhibit robust, strongly enhanced ( 5 × 10 9 ) spectra that are highly dependent on the nanostructured metal (Au or Ag). Although the relative intensities of the 785‐nm SERS vibrational spectral features are very similar for all observed PPIX‐based compounds, the relative intensities are dramatically different on Au and Ag SERS substrates. Time‐dependent density functional theory (TDDFT) calculations are carried out for Au2 /Ag2 –PPIX complexes to understand the origins of this chemical enhancement contribution to the observed SERS spectra. The observed metal dependence of the SERS spectra in the heme ring stretching region (1, 500–1, 620 cm −1 ) are reproduced by calculated resonance Raman intensities due to low‐lying metal (σ) to molecule (π*) charge transfer excitations of the metal dimer–PPIX complexes when the metal dimer is near a porphyrin ring Cβ position. The nuclear coordinate dependence of electronic transition moments is essential for capturing the effects of these CT excitations. A simple method for determining the importance of the transition moment normal mode dependence relative to Franck–Condon factors (A term) is described and implemented. The consequences of this vibronic analysis for the observation of overtone/combination bands in SERS spectra are discussed. Abstract : Differences between the 785‐nm SERS spectra of protoporphyrin IX on Au and Ag substrates arise from a chemical enhancement effect. Time‐dependent density functional theory calculations are carried out for Au2 /Ag2 ‐PPIX complexes and good agreement with experiment is found for the relative intensities of the heme ring stretching modesdue to resonant contributions of low‐lying metal to π* charge transfer states. Including the transition moment nuclear coordinate dependence is essential to capture the Raman contributions of these weak charge transfer excitations